Mediation effects of career aspiration on the relationships of perceived supervisor supports and mastery motivation among extension agents in Iran - Karami, Roya; Ismail, Maimunah; Badsar, Mohammad (2012)
The main objective of this study is to examine the mediation effects of career aspiration on the relationships between supervisors' supports and mastery motivation. Using a sample of 303 extension agents from Jihad-e-Agriculture organizations in Iran, a survey was conducted. The data were analyzed using Structural Equation Modeling (SEM). The results show that the direct path from a supervisor's work support to mastery motivation and career aspiration is significant. The direct path from a supervisor's non-work support to career aspiration is significant while it is not significant for mastery motivation. The assessment of mediation effects of career aspirations show that although the degree of mediation effect of career aspiration for supervisors' work support and mastery motivation is partial, but career aspiration fully mediates the relationship of supervisors' non-work support and mastery motivation. This study has implications on managing extension agents by extension organizations in Iran.